2010
DOI: 10.1016/j.ijid.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Severe group A streptococcal toxic shock syndrome presenting as primary peritonitis: a case report and brief review of the literature

Abstract: Streptococcal toxic shock syndrome (STSS) can be defined as a septic shock syndrome resulting from infection with toxin-producing group A streptococci (GAS). STSS can sporadically present as primary peritonitis in previously healthy persons. Signs of STSS are non-specific and patients generally present with flu-like symptoms and can develop a life-threatening toxic shock syndrome in just a few hours. Diagnosis is mainly by a combination of physical examination, laboratory/culture results, and exclusion of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
1
22
0
2
Order By: Relevance
“…Neutrophils constitute the first line of defense against invading microorganisms but excessive activation and infiltration of neutrophils is also known to be a rate-limiting step in acute lung injury [7,8]. It is widely considered that the lung is the most critical organ involved in STSS patients [9,10]. Extravascular accumulation of neutrophils at sites of inflammation is regulated by adhesion molecules, including P-selectin and Mac-1 as well as CXC chemokines, such as macrophage inflammatory protein-2 (MIP-2) and cytokine-induced neutrophil chemoattractant (KC) [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils constitute the first line of defense against invading microorganisms but excessive activation and infiltration of neutrophils is also known to be a rate-limiting step in acute lung injury [7,8]. It is widely considered that the lung is the most critical organ involved in STSS patients [9,10]. Extravascular accumulation of neutrophils at sites of inflammation is regulated by adhesion molecules, including P-selectin and Mac-1 as well as CXC chemokines, such as macrophage inflammatory protein-2 (MIP-2) and cytokine-induced neutrophil chemoattractant (KC) [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…GAS virulence factors aid in evading phagocytosis and facilitate in adherence to host cells, leading to colonization and invasion of the host [26, 31-35]. In addition, GAS has a family of bacterial antigens that are associated with streptococcal toxic shock syndrome (STSS) [36, 37]. This family includes SpeA (Streptococcal pyogenic exotoxin A), SpeC, and others that bind to the MHC class II molecules and T cell receptors, resulting in an excessive release of immunomodulators that activate complement, coagulation, and fibrinolytic cascades, resulting in toxic shock and death.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathophysiological mechanisms behind streptococcal toxic shock syndrome (STSS) remain elusive, convincing data have demonstrated that soluble streptococcal M protein of the M1 serotype is not only a potent activator of innate immunity, including activation of neutrophils (20) and monocytes (35), but also that the M1 serotype is predominantly linked to fatal STSS (18,25). It is well recognized that the lung is the most sensitive and critical organ affected in STSS patients (51)(52)(53). In fact, acute lung injury continues to constitute a significant cause of morbidity and mortality in sepsis despite aggressive surgical interventions as well as antibiotic and immunomodulating therapies.…”
mentioning
confidence: 99%